2000
DOI: 10.1097/00007632-200011150-00008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cervical Spine in the Polytrauma Patient

Abstract: A standardized protocol to safely and effectively clear the cervical spine has yet to be established. Preliminary results of a new protocol to safely evaluate the cervical spine in the polytrauma patient are promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…In a recent UK survey of intensive care units, 48% of respondents were satisfied to clear the cervical spine while patients were unconscious and unable to provide clinical clues [115], and in published studies, 12-95% of clinicians have been confident in excluding injury with this view alone [12,98,116]. While the prevalence of this practice may vary, with a sensitivity of only 85% among an unconscious polytrauma population with a > 10% prevalence of cervical spine injury, missing at least 1.5% of injuries is unacceptable.…”
Section: Cervical Spine Imaging Modalitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent UK survey of intensive care units, 48% of respondents were satisfied to clear the cervical spine while patients were unconscious and unable to provide clinical clues [115], and in published studies, 12-95% of clinicians have been confident in excluding injury with this view alone [12,98,116]. While the prevalence of this practice may vary, with a sensitivity of only 85% among an unconscious polytrauma population with a > 10% prevalence of cervical spine injury, missing at least 1.5% of injuries is unacceptable.…”
Section: Cervical Spine Imaging Modalitiesmentioning
confidence: 99%
“…Following normal baseline plain films or directed CT, published studies use varying combinations of axial stress, i.e. traction along the line of the cervical spine, to reveal joint space widening [116] and ⁄ or flexion ⁄ extension views. Dynamic fluoroscopy must be distinguished from static maximal flexion ⁄ extension views, which are inherently unsafe in the unconscious as the spine is not imaged during mobilization.…”
Section: Dynamic Fluoroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…3 In addition, several authors cited the location of the separation and longitudinal studies document- ing the eventual posttraumatic development of OO in patients whose cervical spine radiographs were initially normal after the injury. [81][82][83] One of the examples is that of Schuler et al 82 report in 1991, which documented the development of OO after a significant period of trauma. This study reported the natural history of the abnormality observed in a 2-year-old girl who experienced neck pain after a significant fall.…”
Section: Introductionmentioning
confidence: 99%